FORAGE PRODUCTION AND NUTRITIONAL QUALITY OF GRASSES IN MESIC CLIMATE OF POTHWAR PLATEAU, RAWALPINDI - M. Arshadullah; J. Afzal; M. Anwar; S. N. Mirza; M. Rasheed National Agricultural Research Centre; Islamabad. (Journal of Animal and Plant Sciences, 2012)
Forage production and quality of our degraded rangelands need to be improved for enhancing livestock production to meet the ever increasing demand of growing human population for animal protein and other products. A field experiment was conducted at Forestry and Range Management Research field, PMAS-Arid Agriculture University Rawalpindi to evaluate the performance of three grass species under irrigated conditions during 2006-2007. Green Panic Cv. Tanzania, Mott grass and Rhodes grass were tested for sprouting percentage, fresh and dry biomass production, percent moisture contents, forage quality and total digestible nutrients during spring and monsoon season of 2006-2007. The experiment was planned in randomized complete block design (RCBD) in factorial arrangement. Data on fresh and dry matter were collected from the same plots in spring 2006 and monsoon 2007. Three quadrates were harvested randomly for fresh and dry matter determination. Forage quality parameters of grass samples were determined using standard procedures of analysis. Among these grasses Mott grass attained the highest sprouting percentage (86.5%) on average basis followed by Green Panic grass (85.0%). Maximum fresh biomass (229.16 t ha-1) and dry matter yield of (75.67 t ha-1) was also attained by Mott grass during monsoon, 2007. Similar trend was shown during spring 2006 but the yield was more in monsoon than spring, probably due to prolonged growth period and more rainfall. Mott grass got the top position in attaining crude protein (6.74%) and total digestible nutrients (58.02%). Hence, Mott grass is recommended for further propagation in the climate.
Keywords: Promising grasses; mesic climate; forage production; moisture contents; crude protein; total digestible nutrients